2015
DOI: 10.1002/oby.21253
|View full text |Cite
|
Sign up to set email alerts
|

Altered intestinal neuroendocrine gene expression in humans with obesity

Abstract: Objective: Gastrointestinal hormones are critically involved in the regulation of food intake and body weight. Previous studies support an interplay between gastrointestinal hormones and the serotonergic system. This study explored intestinal neuroendocrine expression patterns in humans with obesity versus nonobese humans. Methods: Jejunum samples were collected from 164 humans with obesity (120 women; BMI (mean 6 SD): 43.5 6 6.6 kg/m 2 ) while they underwent Roux-en-Y gastric bypass surgery and from 18 nonobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…In this study, we measured 21 inflammatory markers in the blood, finding that the interleukins 1Ra, 8, and 12, as well as the monocyte chemoattractant protein 1 (MCP1), are elevated in the humans with obesity compared with the non‐obese humans (Table ). We also correlated these elevated inflammatory markers with the markers we measured in the blood, namely active ghrelin, leptin, and 5HT, and we found a significant negative correlation of IL1Ra and leptin ( r = −0.724; p < 0.05) in obese individuals.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In this study, we measured 21 inflammatory markers in the blood, finding that the interleukins 1Ra, 8, and 12, as well as the monocyte chemoattractant protein 1 (MCP1), are elevated in the humans with obesity compared with the non‐obese humans (Table ). We also correlated these elevated inflammatory markers with the markers we measured in the blood, namely active ghrelin, leptin, and 5HT, and we found a significant negative correlation of IL1Ra and leptin ( r = −0.724; p < 0.05) in obese individuals.…”
Section: Resultsmentioning
confidence: 75%
“…F). Since circulating ghrelin is produced predominantly in the stomach, we measured active ghrelin in the serum, which appears to be reduced in the obese individuals, although not significantly ( p = 0.06) as compared with the non‐obese group (obese: 338.3 ± 38.3 pg/mL; non‐obese: 534.6 ± 91.46 pg/mL) …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Findings from a recent study by Ritze et al[162] studying the gene expression of several proteins in the intestinal neuroendocrine network go some way to suggest intestinal GLP-1 expression and/or function may be altered in obesity. Though GLP-1 was not directly tested in the study, the anorectic neuropeptide PYY shown to co-localise and be co-secreted with GLP-1 in enteroendocrine cells[163] was tested.…”
Section: A Role For Glp-1 In the Pathophysiology Of Clinical Obesitymentioning
confidence: 99%
“…Though GLP-1 was not directly tested in the study, the anorectic neuropeptide PYY shown to co-localise and be co-secreted with GLP-1 in enteroendocrine cells[163] was tested. Taking PYY levels as proxy measures of GLP-1, Ritze et al[162] report significant correlations between GLP-1 with the GLP-1R in non-obese subjects (suggesting physiological ligand-receptor signalling), a correlation lost in obese subjects and replaced by correlations with the orexigen ghrelin ( P < 0.01). Ritze et al[162] also observed correlations between the long-term satiety signal leptin and GLP-1R in obese subjects not seen in their lean counterparts.…”
Section: A Role For Glp-1 In the Pathophysiology Of Clinical Obesitymentioning
confidence: 99%